ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN SISWA DI UPT SDN 16 PASAR SUNGAI TUNU PESISIR SELATAN - Mayenti, Susanti Fitri (STKIP Pesisir Selatan, 2025)
According to constructivism theory, reading is not merely a passive activity of receiving information, but also an active activity in constructing meaning based on students' experiences, knowledge, and cognitive abilities. Thus, students who have good reading comprehension skills will more easily grasp the essence of the reading, identify important information, make inferences, and draw conclusions. This study aims to analyze the reading comprehension skills of elementary school students, the factors that influence them, and the relationship between reading interest and students' reading comprehension. The study was conducted at the UPT SDN 16 Pasar Sungai Tunu using a qualitative descriptive method. Data collection techniques included observation, interviews, and documentation with key informants, namely students, teachers, the principal, and parents. The study shows that students' reading comprehension skills are still relatively low, especially in finding the main idea. Internal factors such as reading interest, vocabulary mastery, and learning strategies, as well as external factors such as teacher teaching methods and family environment, play a major role in shaping students' comprehension. This study provides an in-depth understanding of the factors that influence reading comprehension skills at the elementary school level and emphasizes the importance of synergy between families and schools.